Prospects and Challenges of E-banking in Nepal - Banstola, Amrit (Journal of Nepalese Business Studies, 2008)
Financial Institutions are slowly moving from Brick and Mortar (Physical branches) to click and Brick (E-banking). ATM's are the most popular electronic delivery channel for banking services in Nepal. Only few customers are using internet banking facilities. Nepalese financial institutions till date have not faced any kind of electronic fraud or risk. Banks have basic security tools like firewall, lightening/power surge protection. But it is found that the some banks are in lack of having regular back up of website information and E-banking policy. Nepalese banks are using E-banking for their own convenience and for the purpose of retaining exiting customers. The cost analysis of most of the banks in Nepal is seems to be either inadequate or not applied due to their narrow space of business transaction or lack of sufficient tools. No significant correlation was found between use of E-banking and gender, marital status or salary of customer. However, Use of E-banking signification association was found with age and education.The Journal of Nepalese Business Studies Vol. IV, No.1(2007) pp. 96-104